Optimization Strategy for Mudharabah Financing in Indonesian Islamic Banking - Khoirul Umam; Farah Khoirunnisa; Imam Kamaluddin; Isma Aulia Roslan (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
Mudharabah financing in Islamic banking plays a crucial role in addressing real-sector capital problems through its profit and loss sharing (PLS) system. However, despite its potential, the PLS system faces several obstacles that make it less attractive to financial institutions. This study aims to identify the issues causing non-optimal mudharabah financing practices in Indonesian Islamic banking, analyze solutions, and provide the optimization strategies. This study employed a qualitative method with the Analytical Network Process (ANP) approach to analyze the priority issues and solutions to mudharabah financing practices in Indonesia. The data were collected through interviews and focus group discussions with industry experts and stakeholders. The findings show that the primary issues are: 1) internal problems such as non-collateral for long-term profit sharing for small financing customers, and 2) external problems including regulatory issues regarding the COVID-19 stimulus. The study identified priority solutions to overcome these issues, including long-term financing with profit-sharing ratios and yield benchmarks, regulatory strategies, community training, and IT and HR investments. Developing the integrated MSME segment and strengthening stakeholder synergy were also identified as crucial. The study recommends that Islamic banks in Indonesia implement the identified priority solutions to increase trust in mudharabah financing and thus become the core product for financing real-sector capital problems in Indonesia. These findings have important implications for the regulatory authorities and policy-makers to facilitate a conducive environment for Islamic banking and to address the challenges faced by Islamic financial institutions.======================================================================================================== ABSTRAK – Strategi Optimisasi Pembiayaan Mudharabah pada Perbankan Syariah di Indonesia. Pembiayaan mudharabah dalam perbankan syariah memainkan peranan penting dalam menangani masalah permodalan sektor riil melalui pola bagi hasilnya. Namun, meskipun memiliki potensi, sistem bagi hasil kurang menarik bagi lembaga keuangan karena beberapa kendala dalam implementasi. Penelitian ini bertujuan untuk mengidentifikasi permasalahan optimalisasi pembiayaan mudharabah, menganalisis solusi, dan memberikan strategi optimisasinya pada perbankan syariah di Indonesia. Penelitian ini menggunakan metode kualitatif dengan pendekatan Analytical Network Process (ANP) dimana data-data dikumpulkan melalui wawancara dan FGD dengan pelaku industri dan pemangku kepentingan lainnya. Kajian ini menemukan bahwa penyebab utama permasalahan tersebut adalah: 1) faktor internal, seperti tidak adanya jaminan untuk berbagi keuntungan jangka panjang bagi pelanggan pembiayaan kecil, dan 2) faktor eksternal, seperti regulasi terkait stimulus COVID-19. Solusi prioritas dalam mengatasi masalah ini adalah pembiayaan jangka panjang yang menciptakan rasio bagi hasil dan merancang benchmark imbal hasil; strategi regulasi; pelatihan masyarakat; dan investasi TI dan SDM. Selain itu, pengembangan segmen UMKM terintegrasi dan penguatan sinergi pemangku kepentingan juga diidentifikasi sebagai hal yang uregn dilakukan. Penelitian ini merekomendasikan agar bank syariah di Indonesia dapat menerapkan solusi prioritas tersebut agar meningkatkan kepercayaan dan menjadi produk inti untuk pembiayaan sektor riil di Indonesia. Temuan ini memiliki implikasi penting bagi otoritas regulasi dan pembuat kebijakan untuk menciptakan lingkungan yang kondusif bagi perbankan syariah dan mengatasi tantangan yang dihadapi oleh lembaga keuangan syariah.